(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
At the end of 2019, China exploded COVID-19 and mushroomed rapidly throughout every nation. Due to the information received by the media, this message has spread somewhere in the minds of the people. Covid-19 is a complicated, difficult to treat, or horrifying disease. Although the severity of symptoms and the lethality of the virus directly causing the disease cannot be ruled out or ignored, but somewhere, the negligence of the imbalance in the nature of the basic elements of the body is the reason for the fatality of this disease. According to Aacharya Charak, "there can be hundreds of alternatives for the pathogen of any disease," but "this body is the only option for pathogens to cause hundreds of diseases." Which is why this should be the major focus for treatment in any stream of medical science and Ayurveda is a science of ’ayu’, meaning harmony of health and life or journey of healthy life. This reveals that there is a high opportunity to evaluate the range of relevant drugs available in the Ayurvedic that may be employed more rationally to complement each stage of the disease. The Ayurvedic literature provides no explicit mention of this illness but according to the similarity of symptoms despite the occurrence of diseases, there is a special outbreak of Vata and Kapha. This disease can be reconciled in Janpadudhwansh janya diseases, Visham jwara and Vatshleshmic jwara.